(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
We must reduce our consumption of fossil fuels. Bioethanol is derived from crops, such as annual and perennial dry energy grasses, as well as forestry waste. The hydrolysis of lignocellulosic biomass enzymes yields fermentable sugars, but, this process necessitates costly pretreatment and energy consumption. Utilizing bioethanol derived from cannabis plants could potentially address the issues surrounding the use of lignocellulosic biomass. Weeds are suitable for use as bioenergy feedstock because they grow quickly and have a high concentration of glucose. The work resulted in the creation of Chenopodium album biofuel. The physicochemical analysis revealed elevated levels of volatile solids, minimal ash content, and an augmented presence of cellulosic and hemicellulosic compounds, indicating a promising potential for bioenergy production. Acid pretreatment resulted in a higher amount of fermentable sugars for biohydrogen and biomethane production compared to alkaline pretreatment. Additional preliminary investigations were conducted utilizing a 1% (w/w) solution of sulphuric acid at a temperature of 121 °C for a duration of 15 minutes. Acid-treated materials exhibited perforations and expanded structures on scanning electron microscopy (SEM). Therefore, the cellulose underwent intrinsic structural changes as a result of a 1% acid pretreatment, which made it more compatible with microbial activity. The above studies confirm the potential of Chenopodium album for production of biofuel.